A Comparative Analysis of the Leadership Behavior of Ward Managers in Critical Care and Non-Critical Care Units at a Private Hospital - Ngongoloy, Hesky Frengky (Jurnal Ragam Pengabdian, 2026)
Nurse performance is a key indicator of nursing care quality and patient safety in hospitals. One managerial factor that may influence nurse performance is the leadership style of head nurses. Differences in work characteristics between critical and non-critical care units require appropriate leadership approaches to maintain optimal staff performance. This study aimed to analyze the relationship between head nurses’ leadership styles in critical and non-critical care units and nursing staff performance at Siloam Hospital Manado. This study employed a quantitative approach with a correlational cross-sectional design. The sample consisted of 110 nurses and midwives working in critical and non-critical units at Siloam Hospital Manado, selected using a purposive sampling technique. Data were collected using validated and reliable questionnaires on leadership style and nurse performance. Data analysis was conducted using the Chi-Square test and contingency coefficient. The findings showed that democratic leadership was the most dominant leadership style perceived by respondents in both critical and non-critical units. The Chi-Square test result revealed a p-value of 0.065 (p > 0.05), indicating no statistically significant relationship between leadership style and nurse performance. The contingency coefficient value of 0.217 indicated a weak association between the two variables. Conclusion: Head nurses’ leadership at Siloam Hospital Manado is predominantly democratic. However, statistically, leadership style was not significantly associated with nursing staff performance. Nurse performance appears to be more strongly influenced by other factors such as professional competence, nursing practice standards, and hospital work systems.